Assessment of access and outcomes of kidney transplantation through the reforms of the Swiss organ allocation system - Massimiliano Bertacchi; Sylvie Ferrari-Lacraz; Jakob Nilsson; Agim Thaqi; Yvan Schmutz; Caroline Wehmeier; Thomas Schachtner; Thomas Mueller; Dela Golshayan; Julien Vionnet; Stefan Schaub; Fadi Haidar; et al. (Frontiers in Public Health)
IntroductionThe Swiss allocation system for kidney transplantation has evolved over time to balance medical urgency, immunological compatibility, and waiting time. Since the introduction of the transplantation law in 2007, which imposed organ allocation on a national level, the algorithm has been optimized. Initially based on waiting time, HLA compatibility, and crossmatch performed by cell complement-dependent cytotoxicity techniques, the system moved in 2012 to a score including HLA compatibility, waiting time, anti-HLA antibodies detected by the Luminex® technology, and a virtual crossmatch. In 2015, the score was optimized to balance the impact of preemptive listing and HLA matching of hyperimmunized recipients.MethodsWe reviewed access to transplants and post-transplant outcomes along those changes, defining three periods (v0: 2007–2012, v1: 2012–2015, v2: 2015–2020).ResultsChanges in the Swiss allocation system improved the fairness of access to transplantation, particularly for hyperimmunized patients. However, the system still fails to grant fair access to some blood groups. Furthermore, our data showed that rule modifications did not impact early post-transplant complications, maintaining similar time to first rejection and 1-year graft survival across subgroups.DiscussionSuch an analysis is useful for validating changes made to the allocation system and identifying aspects that need to be implemented in future revisions.